Bevacuzimab May Be Less Effective in Obese Metastatic Colorectal Cancer Patients - (:unkn) unknown (SPRINGER, 2019)
PurposeThe purpose of this study was to investigate whether obesity affects survival in metastatic colorectal cancer (mCRC) patients treated with bevacizumab combined with chemotherapy.MethodsA total of 563 patients with mCRC who had received first-line chemotherapy in combination with bevacizumab were studied. Patients were grouped as obese (BMI levels >30) or non-obese (BMI levels <30). Progression-free survival (PFS) and overall survival (OS) were analyzed. Primary tumor location was also investigated in terms of PFS and OS.ResultsThe median age of the patients was 59years. The non-obese group had longer PFS than the obese group (P=0.030). The 2-year survival rate of the non-obese group was also significantly higher (P=0.036). The median PFS of non-obese patients was significantly longer in Kras wild-type patients (10.1 vs. 8.1months, P=0.010). Among patients with left-sided primary tumor location, median PFS and OS were significantly higher in the non-obese group (PFS non-obese, 11.5months; obese, 8.8months; P=0.002) (OS non-obese, 29.4months; obese, 21.4months; P=0.026).ConclusionsEfficacy of bevacizumab may be lower in obese patients. Among patients with Kras wild-type left-sided tumors treated with bevacizumab-based regimens, the prognosis could be worse for obese patients than that for non-obese patients. There is a need for prospectively designed studies of obese patients to prove the efficacy and dosages of bevacizumab in treatment of mCRC.
Keywords: Metastatic colorectal cancer; Bevacizumab; Body mass index; Obesity; K-ras; BODY-MASS INDEX; PHASE-III; BEVACIZUMAB; CHEMOTHERAPY; CAPECITABINE; OXALIPLATIN; SURVIVAL; ANTIBODY; BMI; FAT